Brain Drain: Factors Influencing Students’ Intention to Leave Nepal - Khatri, Chudamani (Tribhuvan University Journal, 2026)
Brain drain is a major and emerging concern for most developing countries. Nepal is especially vulnerable to this trend due to its growing youth demographic and the expanding higher education sector. There is increasing interest among students in academic and professional opportunities abroad, which could potentially reduce Nepal’s intellectual capital and future leadership. The main objective of this paper is to explore the factors influencing students’ intention to leave Nepal from a brain drain perspective. The research was conducted within a positivist paradigm using a causal-comparative research design to examine objective reality. The questionnaire survey was conducted on 412 students in Nepal through convenience sampling. The data analysis was based on demographic, descriptive and inferential statistics, measurement and structural equation modeling (SEM) using SPSS and Smart PLS 4.1.1.2. Friends’ influence, salary, and working environment are important factors that drive brain drain intentions among students. On the other hand, the research found that career opportunities did not have a statistically significant effect on students’ decisions to emigrate. Study and employment opportunities abroad are strong motivations for students to leave Nepal. This study has significant implications for the government of Nepal, policymakers and schools and colleges in Nepal.